Does Risk Management Improve Financial Performance? Empirical Evidence from Indonesian Listed Banks - Candera, Mister; Safitri, Ervitas; Feryaldo, Rozzy (Innovation, Technology, and Entrepreneurship Journal, 2026)
This study aims to test and analyze the influence of risk management on financial performance in banking sector companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with secondary data. The study population consisted of 47 banking companies, with a sample of 19 companies selected using purposive sampling techniques over five years, resulting in 95 data observations. The analysis methods used include multiple linear regression, F test, t test, and determination coefficient. The results of the study show that risk management has a significant effect on financial performance. Partially, credit risk and liquidity risk have a positive and significant effect on financial performance, while operational risk has a negative and significant effect on financial performance. A determination coefficient (R²) value of 32.2% indicates that variations in financial performance can be explained by risk management variables, while the rest is influenced by other factors outside the research model.